Case Report on Anorexia Nervosa in a Pakistani 14 Years Old Boy - Hussain, Zainab; Anwer, Rabia (Archives of Clinical and Biomedical Research, 2017)
Anorexia nervosa is an eating disorder characterized by a low weight, fear of gaining weight, a strong desire to be thin, and food restriction. Many people with anorexia see themselves as overweight even though they are underweight. Often they weigh themselves frequently, eat only small amounts, and only eat certain foods. Some will exercise excessively, force themselves to vomit, or use laxatives to produce weight loss. Complications may include osteoporosis and infertility and women may suffer from amenorrhea. A 14-years old boy, student of class 8, resident of Larkana was referred to us for dietary counseling. He had minimal or no intake of food since last two months, lost 20kgs in past 2 years, was weighing himself repeatedly since past two months and was doing excessive exercise. A well defined interview with his parents was done and the diagnosis of anorexia nervosa was made.